Methods for Strengthening Memorization Based on Ta’lim al-Muta’allim and Their Scientific Relevance - Subekti, Fiqi Restu; Wibowo, Taufik Awan (South Sulawesi Education Development, 2025)
The capacity to memorise plays a pivotal role in Islamic educational tradition, particularly in the preservation of the authenticity of teachings through the transmission of the Qur’an and hadith. In the literary work Ta’lim al-Muta’allim, composed by al-Zarnuji, a seminal text in its field, a range of methodologies is presented for the purpose of enhancing memory. These methodologies encompass a variety of approaches, including diligent study, augmented worship, and the ingestion of specific substances such as honey, kundar, and red wine. The present study aims to examine these methods scientifically in order to determine their relevance to contemporary findings. Utilising a literature review and content analysis approach, this study examines the text of the book Ta’lim al-Muta’allim and compares it with the results of recent scientific research in the fields of cognitive science and health. The findings of the study demonstrate that the methods employed to enhance memory in the book can be categorised into three distinct classifications. Firstly, there is a need to acknowledge the scientific methods that have been proven to be effective. Such methods include diligent study, increasing worship, and consuming honey. Secondly, methods with potential scientific validity, such as the consumption of kundar and red wine, which have shown positive results in some preliminary studies, are also recommended. Thirdly, there are methods that have yet to be scientifically validated. These include the use of a miswak, reducing food intake, and consuming foods that reduce phlegm. These findings suggest that some of the classical educational heritage in the book remains relevant and can be integrated with modern scientific approaches. Consequently, al-Zarnuji’s treatise is not only spiritually valuable but also has the potential to contribute to the development of contemporary learning methods.